Mapping the Maqasid Index in Islamic Banking: A Bibliometric Analysis of Scopus based Literatures - Nashruddin, Ahmad (SMART Insight, 2025)
This paper analyses how the Maqasid Index has been used to evaluate Islamic banking performance by conducting a bibliometric study of Scopus-indexed publications in the economics domain. From an initial pool of 544 documents related to Maqasid Sharia and Islamic finance, 101 publications classified in economics and closely related areas were retained for detailed analysis. Using Biblioshiny (Bibliometrix in R) and VOSviewer, the study examines publication trends, citation performance, keyword co-occurrence networks, and thematic evolution. The results show a strong and accelerating growth of research on Maqasid-based performance evaluation since around 2018, with “Islamic bank(ing)”, “Maqasid Shariah”, “performance”, “Indonesia”, and “Malaysia” emerging as dominant terms. Network and density maps reveal five main clusters: (i) performance and profitability, (ii) Islamic banking applications, (iii) Indonesian content-analysis studies, (iv) Shariah governance and compliance, and (v) ethics, religiosity and sustainability. Treemap and word-cloud visualisations confirm that the core of the literature lies at the intersection of Islamic banking, Maqasid al-Shariah and performance, with governance and sustainability becoming increasingly important. The paper contributes by (i) mapping the economics-focused Maqasid Index literature, (ii) clarifying its thematic and geographical structure, and (iii) identifying gaps and implications for future research and industry practice.